Meta-analyses of the effects of DPP-4 inhibitors, SGLT2 inhibitors and GLP1 receptor analogues on cardiovascular death, myocardial infarction, stroke and hospitalization for heart failure. (April 2019) - Sinha, Binayak; Ghosal, Samit
Abstract: Aim: To assess the effects DPP-4i; SGLT2-i & GLP1-RA on CV death, MI, stroke and hHF. This is probably the first meta-analysis to assess the effects of these drugs on MI and stroke in totality, including non-fatal & fatal MI and stroke. Methods: Scientific databases were searched for RCTs with pre-specified inclusion criteria and each end-point from the selected 13 studies was reported as an effect size (M H odds ratio) with a 95% confidence interval P value. Results: The pooled analysis of all the 5 available CVOT with DPP-4i resulted in a neutral effect on MI, stroke, the combined end points of MI & Stroke, CV death and hHF. The pooled analysis of all the 5 available CVOTs with GLP1-RA resulted in a neutral effect on MI. However, there was a statistically significant 12% reduction in CV death (P = 0.01), 13% reduction in stroke (P = 0.02) and 11% reduction the combined end points of MI & Stroke (P = 0.001). The impact of GLP1-RA inhibitors on hHF was neutral. The pooled analysis of all the 3 available CVOTs with SGLT2-i resulted in a neutral effect on MI, stroke, the combined end points of MI & Stroke and CV death. There was however a statistically significant 28% reduction in hHF (P < 0.001). Conclusion: DPP-4i & SGLT-2i are neutral as far as all aspects of CV outcomes are concerned except for hHF which is significantly reduced by the latter. GLP1-RA as a class reduce risk of ASCVD showing a significant reduction in MI and stroke.